Effects of the Exopolysaccharide from Lactiplantibacillus plantarum HMX2 on the Growth Performance, Immune Response, and Intestinal Microbiota of Juvenile Turbot, Scophthalmus maximus - Gege Hu; Yihui Wang; Rui Xue; Tongji Liu; Zengjia Zhou; Zhennai Yang (Foods, 2023)
In this study, the exopolysaccharide (EPS) from Lactiplantibacillus plantarum (HMX2) was isolated from Chinese Northeast Sauerkraut. Its effects on juvenile turbot were investigated by adding different concentrations of HMX2-EPS (C: 0 mg/kg, H1: 100 mg/kg, H2: 500 mg/kg) to the feed. Compared with the control group, HMX2-EPS significantly improved the growth performance of juvenile turbot. The activities of antioxidant enzymes, digestive enzymes, and immune-related enzymes were significantly increased. HMX2-EPS could also increase the secretion of inflammatory factors and enhance the immune response of turbot by regulating the IFN signal transduction pathway and exhibit stronger survival rates after the A. hydrophila challenge. Moreover, HMX2-EPS could improve the diversity of intestinal microbiota in juvenile fish, increase the abundance of potential probiotics, and reduce the abundance of pathogenic bacteria. The function of gut microbes in metabolism and the immune system could also be improved. All results showed better effects with high concentrations of HMX2-EPS. These results indicated that HMX2-EPS supplementation in the diet could promote growth, improve antioxidant activity, digestive capacity, and immunity capacity, and actively regulate the intestinal microbiota of juvenile turbot. In conclusion, this study might provide basic technical and scientific support for the application of L. plantarum in aquatic feed.